Pengaruh Pengujian Hardening pada Baja Karbon Rendah Sebagai Solusi Peningkatan Kualitas Material: - Nurlina, Nila (Universitas Islam Balitar Blitar, 2019)
Low carbon steel is an alloy consisting of the main elements of carbon with a low composition and iron. The mechanical properties of low carbon steel are influenced by the composition and microstructure of metals. One of the mechanical properties of the metal to be searched for is violence. The purpose of this study is to conduct hardening testing of low carbon steel material. The results obtained from this study are that the hardness of low carbon steel increases with increasing heating temperature. In addition, based on experimental data it is known that salt water cooling media has a higher hardness compared to SAE 10 oil.